1991
DOI: 10.1073/pnas.88.23.10662
|View full text |Cite
|
Sign up to set email alerts
|

CD10/neutral endopeptidase 24.11 hydrolyzes bombesin-like peptides and regulates the growth of small cell carcinomas of the lung.

Abstract: Bombesin-like peptides are essential autocrine growth factors for many small cell carcinomas (SCCas) of the lung. Herein, we demonstrate that these malignant pulmonary neuroendocrine cells express low levels of the cell surface metalloendopeptidase CD10/neutral endopeptidase 24.11 (CD10/NEP, common acute lymphoblastic leukemia antigen)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
164
2
2

Year Published

1996
1996
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(177 citation statements)
references
References 45 publications
9
164
2
2
Order By: Relevance
“…However serum levels of ACE activity and the ACE levels in BCF showed an inverse correlation, which suggests that ACE in BCF is not derived by uptake from the circulation and probably originates from a local source. (Shipp et al, 1991) and as GRP and bombesin are potent growth-promoting factors for a wide variety of cancers (reviewed in Schrey and Patel, 1994) it seems possible that a reduction of enkephalinase expression by cancer cells is necessary for GRP to have a mitogenic effect. Indeed the growth of bombesin-dependent small-cell lung carcinomas is stimulated by enkephalinase inhibitors and reduced by exogenous enkephalinase (Shipp et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However serum levels of ACE activity and the ACE levels in BCF showed an inverse correlation, which suggests that ACE in BCF is not derived by uptake from the circulation and probably originates from a local source. (Shipp et al, 1991) and as GRP and bombesin are potent growth-promoting factors for a wide variety of cancers (reviewed in Schrey and Patel, 1994) it seems possible that a reduction of enkephalinase expression by cancer cells is necessary for GRP to have a mitogenic effect. Indeed the growth of bombesin-dependent small-cell lung carcinomas is stimulated by enkephalinase inhibitors and reduced by exogenous enkephalinase (Shipp et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…(Shipp et al, 1991) and as GRP and bombesin are potent growth-promoting factors for a wide variety of cancers (reviewed in Schrey and Patel, 1994) it seems possible that a reduction of enkephalinase expression by cancer cells is necessary for GRP to have a mitogenic effect. Indeed the growth of bombesin-dependent small-cell lung carcinomas is stimulated by enkephalinase inhibitors and reduced by exogenous enkephalinase (Shipp et al, 1991). GRP is present in BCF (Weber et al, 1989) and is present in higher levels in type 1 fluids, leading to the suggestion that it is a factor in the increased risk associated with type 1 BCF (Lai et al 1990a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…170 The inactivation of such peptides causes a reduction in the local concentrations available for receptor binding and signal transduction. 171 Therefore, loss of NEP results in the failure to inactivate the active peptides. 172 Recently, Papandreou et al 172 have shown that NEP expression and catalytic activity are lost in vitro in androgen-independent but not androgen-dependent prostate cancer cell lines.…”
Section: Neuropeptidesmentioning
confidence: 99%
“…The physiological role of the enzyme depends on available substrates in specific organs and cell types (Shipp and Look, 1993). The enzyme also regulates peptidemediated cellular proliferation by inactivating bombesin or other neuropeptides that are essential autocrine growth factors for certain human solid tumors (Burns et al, 1999;Cohen et al, 1996;Papandreou et al, 1998;Shipp et al, 1991).…”
mentioning
confidence: 99%